SUMBERDAYA PENDORONG KEUNGGULAN BERSAING PERUSAHAAN - Cut Nina Rostina (universitas teuku umar, 2017)
AbstractUnderstanding sources of sustained competitive advantage has become a major area of research in strategic management. Building on the assumptions that strategic resources are heterogeneously distributed across firms and that these differences are stable over time, this article examines the link between firm resources and sustained competitive advantage. Four empirical indicator of the potential of firm resources to generate sustained competitive advantage- value, rareness, imitability, and substitutability- are discussed.Keywords: resources based view, kompetensi, sumberdaya